Co-Parenting und die Zukunft der Liebe: Über post-romantische Elternschaft - Wimbauer, Christine (transcript, 2021)
"Co-parenting" as a family concept is spreading and it thereby challenges the promises of the romantic ideal of love along with its gender-equal normal family model. But what does this mean for love itself? Is it being destroyed or transformed and opened into new forms of family and relationships? Does post-romantic parenthood even unfold a utopian-emancipative potential that frees women and LGBTIQ*s from patriarchal, hetero- and couple-normative relations of domination? In addition to present and future scenarios, Christine Wimbauer also explores the socio-political challenges of these developments.